Online Service Delivery in Survey Offices of Nepal (Journal on Geoinformatics, Nepal, 2022)
The Survey Department of Nepal has started transformation of cadastral management from offline to centralized online system. This has enabled the department to provide the online services to the clients beyond the physical boundaries of Survey Offices. This paper elaborates the present status of online service delivery in different survey offices based on recent policy, institutions and their applications. Data analysis shows that Nepal Land Information System (NeLIS) supports basic norms and values of online service delivery effectively and has become a major milestone in the e-land administration. The provision of assigning different roles and sections inside a survey office has made the system more secure, reliable and responsive. Recently, directives of digital land surveying, mapping and administration for public service delivery have been formulated to address the legal aspect of service delivery. The provision of online application for map, field book and plot register print through https://www.merokitta. dos.gov.np has simplified the working procedure for general public and institutional users too. The expansion of this system in more survey offices along with additional and more advanced features are necessary. Similarly, legal provision of data sharing between Land Records Information Management System (LRIMS) and NeLIS in a meaningful way is also essential in the days to come.